The administrative behavior of directors of teacher preparation institutes and its relationship to the morale of teachers. (Journal of the College of Basic Education, 2023)
The research aims to identify the administrative behavior of directors of teacher training institutes and its relationship to the spiritthe morale of the teachers; To achieve the aim of the research, the researcher put the following two zero hypotheses:1. There is no statistically significant correlation at the level of significance (0.05) between administrative behavior and spirit.morale,2. There are no statistically significant differences at the level of significance (0.05) in the associative relationship between behaviorAdministrative and morale according to the gender variable (male - female).The research community consisted of teachers from teacher training institutes affiliated to the Directorate General for Teacher Preparation.Baghdad, whose number is (660) male and female teachers for the academic year (2011-2012 AD); by (203)teaching and (457) female teachers; The researcher chose a sample of male and female teachers distributed randomlyOver the six general directorates of education in Baghdad, with (24) males and (22) females in Baghdad-Rusafa Educationthe first; and (16) males and (21) females in the breeding of Baghdad-Rusafa the second, and (11) males and (8) in theBaghdad Al-Rusafa third breeding; while Baghdad Al-Karkh first breeding, it reached (23) males and (23) females.(12) males and (12) females in Baghdad Al-Karkh secondary school; And (12) males and (14) females in breedingBaghdad, the third Karkh; They make up 30% of the research community. Thus, it became the final research sample(198) teaching and teaching.Due to the availability of two measures of administrative behavior and morale prepared by Al-Nasser (2004) forThe heads of scientific departments at the University of Baghdad, so the researcher adopted these two measures to achieve the goal of the current researchWhich includes the first scale of (42) items and the second scale includes (26) items; It is located in front of each paragraphThree levels, namely: (high, medium, weak) and these levels take (3 _ 2 _ 1) onrespectively, and thus, the degree of sharpness will be two degrees - while the paragraph that is more than (2,5) is considered high